Effects of radial transport on divertor power and particle flux widths under different operational regimes in EAST. (8th September 2021) - Deng, G.Z.; Xu, X.Q.; Liu, X.J.; Xu, J.C.; Meng, L.Y.; Liu, J.B.; Li, N.M.; Schmitz, L.; Gao, S.L.; Yang, Q.Q.; Ye, Y.; Xia, T.Y.; et al.
Abstract: A study of the effects of radial transport on the outer divertor particle and power flux widths ( λ js and λ q ) is carried out using plasmas under different operational regimes in the Experimental Advanced Superconducting Tokamak (EAST). In the EAST experiments, the λ js values measured during the grassy intra- and inter-ELM phases are similar, and the averaged value of λ js during grassy ELMy discharges is found to be smaller than that of the intra-ELM phase of type-I ELMy discharges but larger than that of the inter-ELM phase of type-I ELMy discharges. Simulations of scans of the radial particle and heat transport coefficients, D and χ e, performed using the BOUT++ transport code show that both λ q and λ js increase with D and χ e, especially when D or χ e is larger than a threshold value, indicating that background turbulence starts to matter in the determination of λ q and λ js when D or χ e surpasses the threshold value. A comparison between the simulation of the D scan and the experimental results shows that the different values of λ js obtained under different plasma operational regimes are probably due to the different intensities of background turbulence, which is beyond the scope of Goldston's heuristic drift-based model as reported by Goldston et al (2012 Nucl. Fusion 52 013009), since their model was derived by assuming that turbulent transport does not exceed a certain level. The ratio of λ js to λ q is greatly affected by the radial transport; however, simulations carried out using Scrape-off Layer Plasma Simulation (SOLPS) show that divertor geometry and plasma density have big influences on λ js, and thus could also affect the ratio of λ js to λ q .